Carbon steel corrosion behaviour in aqueous carbonated solution of MEA/bmim DCA - Barham, H.A. (International Journal of Electrochemical Science, 2011)
Carbon steel corrosion rates were measured in carbonated solution mixtures of monoethanolamine (MEA) and 1-Butyl-3-methylimidazolium dicyandiamide (bmim DCA) and MEA without bmim DCA, using polarization curve and electrochemical impedance spectroscopy (EIS). Corrosion tests were carried out for 4.0 M carbonated MEA and bmim DCA concentration varied from 0.1 to 1.0 M. The CO 2 loading was 0.55 mol/mol and temperature was varied from 40 to 80 °C. Results showed adding bmim DCA decreased the corrosion rate of carbon steel for 4.0 M MEA/bmim DCA system. However, the effect of bmim DCA addition was less as the temperature increased to 80 °C. Scanning Electron Microscope (SEM) and Energy dispersive X-ray analysis (EDX) were also carried out to characterize the surface morphology and corrosion product formed on the electrode surface. The SEM and EDX spectrum showed that a protective corrosion layer has formed on the electrode surface for 4.0 M MEA/bmim DCA system. The corrosion rate of carbon steel was also measured using EIS at 40 °C and 4.0 M MEA/1.0 M bmim DCA with different exposure times. It was found the corrosion rate increased at first, but decreased progressively with time. The results got from EIS agree well with the polarization curve, SEM and EDX.